Psychometric Properties of a Cultural Adapted Version of the Assessment of Identity Development in Adolescence in Panama - González Flores, Sergio; Goth, Kirstin; Díaz-Hernandez, Ruben A. (Frontiers in Psychiatry, 2022)
The Assessment of Identity Development in Adolescence (AIDA) is a self report instrument to detect pathological development of Identity. In Panamá, psychometric instruments for assessment of psychopathology in adolescence are lacking. Our aim was to develop a valid and reliable version of the AIDA Inventory for Panamanian Population. AIDA was adapted to Spanish considering cultural aspects of Panamanian population. Two pilot tests were performed prior to main test to assess item-total correlation at subscale, primary scale and total scale levels and internal consistency at subscale level. A mixed sample of students and patients (N = 315) completed the AIDA inventory, the “Strength and Difficulties Questionnaire – Self Report” and “Defense Style Questionnaire – 40”. AIDA was retested in a sub sample from school population (n = 98). The Structured Clinical Interview for Axis II Disorders was used for diagnosis of personality disorders in the patient sample (n=25). Psychometric properties were tested to assess internal consistency, reliability, factorial validity, convergent validity and criterion validity. AIDA Panama showed excellent internal consistency for Diffusion scale with Cronbach’s α: .94 and retest reliability for Diffusion scale was good with r pearson: .84. A Bifactorial CFA was modelled to assess the dimensionality of the inventory. The proportion between OmegaH and Omega at total scales 96% of the variance is explained by a general factor. Furthermore, the Explained Common Variance for the General Factor is 73% supporting unidimensionality. In line with theory, Diffusion scale showed a high positive correlation (r= .67) with Total Difficulties scale and high positive correlation (r=.71) with Immature Defense scale. The AIDA total score differed highly significant (p= .000) between the patient sample and the students with a large effect size (d= 1.02) Conclusion: The adaptation and validation of AIDA for Panamanian adolescent population was successful with good psychometric properties and significant correlations with psychopathological constructs. AIDA showed significant differences between group samples, discriminating between healthy adolescents and clinical impaired with psychopathology